Elevated pressure influences relative distribution of segmental regions of the trabecular meshwork. (January 2020) - Vranka, Janice A.; Staverosky, Julia A.; Raghunathan, VijayKrishna; Acott, Ted S.
Abstract: Elevated intraocular pressure (IOP) is the primary risk factor for glaucoma and is the only treatable feature of the disease. There is a correlation between elevated pressure and homeostatic reductions in the aqueous humor outflow resistance via changes in the extracellular matrix of the trabecular meshwork. It is unclear how these extracellular matrix changes affect segmental patterns of aqueous humor outflow, nor do we understand their causal relationship. The goal of this study was to determine whether there are changes in the segmental outflow regions with perfusion in normal eyes, and whether these regions change during the IOP homeostatic response to elevated pressure. Using human anterior segment perfusion organ culture, we measured the amount of high flow (HF), intermediate flow (MF), and low flow (LF) regions before and after 7 days of perfusion at either physiologic pressure ("1x") or at elevated pressure ("2x"). We found a small but significant decrease in the amount of HF regions over 7 days perfusion at 1x pressure, and a twofold increase in the amount of MF regions over 7 days perfusion at 2x pressure. Small positional differences, or shifts in the specific location of HF, MF, or LF, occurred on a per eye basis and were not found to be statistically significant across biological replicates. Differences in the amount of segmental flow regions of contralateral eyes flowed at 1x pressure for 7 days were small and not statistically significant. These results demonstrate that perfusion at physiologic pressure had little effect on the distribution and amount of HF, MF and LF regions. However, the overall amount of MF regions is significantly increased in response to perfusion at elevated pressure during IOP homeostatic resistance adjustment. The amount of both HF and LF regions was decreased accordingly suggesting a coordinated response in the TM to elevated pressure. Highlights: Segmental flow regions of the TM are relatively stable after 7 days of perfusion. Intermediate flow regions are increased after perfusion at elevated pressure. These dynamic changes are part of the normal homeostatic response to pressure. Contralateral eyes show small differences in amounts of flow regions.